Microtubular integrity differentially modifies the saturated and unsaturated fatty acid metabolism in cultured hep G2 human hepatoma cells - Marra, Carlos Alberto (2005)
The influence of cytoskeleton integrity on the metabolism of saturated and unsaturated FA was studied in surface cultures and cell suspensions of human Hep G2 hepatoma cells. We found that colchicine (COL), nocodazol, and vinblastin produced a significant inhibition in the incorporation of labeled saturated FA, whereas incorporation of the unsaturated FA remained unaltered. These microtubule-disrupting drugs also diminished Δ9-, Δ5-, and Δ6-desaturase capacities. The effects produced by COL were dose (0–50 μM) and time (0–300 min) dependent, and were antagonized by stabilizing agents (phalloidin and DMSO). Dihydrocytochalasin B (20μM) was tested as a microfilament-disrupting drug and produced no changes in either the incorporation of [14C]FA or the desaturase conversion of the substrates. We hypothesized that the interactions between cytoskeleton and membrane proteins such as FA desaturases may explain the functional organization, facilitating both substrate channeling and regulation of unsaturated FA biosynthesis.